PEMBELAJARAN TAKSONOMI FAUNA DI PERGURUAN TINGGI - Jusup - Subagja (Masyarakat Zoologi Indonesia, 2006)
Subagja, J. 2006. Teaching of fauna taxonomy in university. Zoo Indonesia. Vol.15 (2): 101-105. At the time being fauna taxonomy course in university is unattractive,boring, idle, and is not put in practical use. Apparently the teaching of fauna taxonomyis not in accordance to the development of taxonomy concepts. According to thehistory of taxonomy, since 19409 the concept of taxonomy has developed to bebiological taxonomy or biosystematics. And the development is not implemented inthe current teaching of fauna taxonomy. Therefore, the teaching of fauna taxonomy inuniversity should be corrected. Professional organization, the Society of IndonesianFauna Taxonomy, should take a role actively so the taxonomy will function well.